1993
DOI: 10.1073/pnas.90.14.6874
|View full text |Cite
|
Sign up to set email alerts
|

Genomic mapping with I-Ceu I, an intron-encoded endonuclease specific for genes for ribosomal RNA, in Salmonella spp., Escherichia coli, and other bacteria.

Abstract: Construction of physical maps of genomes by pulsed-field gel electrophoresis requires enzymes which cut the genome into an analyzable number of fragments; most produce too many fragments. The enzyme I-Ceu I, encoded by a mobile intron in the chloroplast 23S ribosomal RNA (rrl) gene of Chlamydomonas eugametos, cuts a 26-bp site in the rrl gene. This enzyme digests DNA of Salmonella typhimurium at seven sites, each corresponding to one of the rrl genes of the rrn operons, but at no other site. These seven fragme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
301
0
3

Year Published

1998
1998
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 328 publications
(315 citation statements)
references
References 18 publications
11
301
0
3
Order By: Relevance
“…The enzyme I-CeuI recognizes a highly conserved 26 bp sequence within the rrl genes of most eubacteria (Liu et al, 1993). Therefore, the digestion of L. acidophilus genomic DNA with I-CeuI into four fragments was indicative of the presence of four rrn operons on the chromosome (Fig.…”
Section: Analysis Of the Rrna (Rrn) Operonsmentioning
confidence: 99%
“…The enzyme I-CeuI recognizes a highly conserved 26 bp sequence within the rrl genes of most eubacteria (Liu et al, 1993). Therefore, the digestion of L. acidophilus genomic DNA with I-CeuI into four fragments was indicative of the presence of four rrn operons on the chromosome (Fig.…”
Section: Analysis Of the Rrna (Rrn) Operonsmentioning
confidence: 99%
“…This enzyme specifically targets genes coding for rRNA (Liu et al, 1993). Hybridization patterns indicated that the resistance gene was located on the chromosome in all transconjugants (data not shown).…”
Section: Kb Erm(b) Orf298 Erm(b) Orf298 Erm(b) Orf298 Erm(b) Orf298 Ementioning
confidence: 95%
“…Genomic DNA embedded in agarose plugs was digested for 3 h at 37°C with 0.01 U of I-CeuI, an intron-encoded endonuclease specific for rRNA genes (20), or overnight at 27°C with 25 U of SmaI. Fragments were separated on agarose gel (1.2% for I-CeuI and 0.8% for SmaI digestion) with a contour-clamped homogeneous electric field DR III system (Bio-Rad Laboratories, Hercules, CA) under the following conditions: total migration, 24 h for I-CeuI or 27 h for SmaI; initial pulse, 60 s for I-CeuI or 5 s for SmaI; final pulse, 120 s for I-CeuI or 35 s for SmaI; voltage, 6 V/cm; included angle, 120°; and temperature, 14°C.…”
Section: Methodsmentioning
confidence: 99%